Ne sine imperio provincia esset (Livio 39.21.4) o come risolvevano i Romani le crisi causate dalla morte di un imperator nella tarda Repubblica - Díaz-Fernández, Alejandro (My University, 2022)
After fourteen months in the command of Cilicia, in July 50 Cicero finally went back to Rome, temporally entrusting his province to his newly arrived quaestor, C. Coelius Caldus. According to a letter sent to M. Caelius Rufus, Cicero decided to leave the command of Cilicia to his quaestor because the latter was a young nobilis and because it was how everyone proceeds (Cic. fam. 2.15.4: at quaestorem, at nobilem adulescentem, at omnium fere exemplo). Cicero’s comment suggests that quaestors usually held the provinces on an interim basis when the imperatores left office. Now, what happened when the command of a province was suddenly vacant by the death of its governor? Who was left in charge until the arrival of the new governor? When talking about the events of 186, Livy alludes to the death of the propraetor C. Atinius in Hispania Ulterior during the siege of Hasta. Apparently, the news caused the rapid reaction of the senate, which immediately sent letters to the praetor C. Calpurnius Piso at the port of Luna with the aim of urging him to hasten his departure, so that the province might not be left without imperium (Liv. 39.21.4: ne sine imperio provincia esset). The quickness with which the senate reacted reveals that the power vacuum caused by the death of an imperator was a critical situation to which it was essential to respond without delay. It is therefore worth asking what happened in Hispania Ulterior from the death of C. Atinius until the arrival of C. Calpurnius Piso. This is not the only case that we know of, so it seems necessary to carry out a study that treats how the Romans tried to resolve these situations of crisis in the provinces during the Late Republic.
Keywords: Roma - Provincias; Roma; Roma - Administración provincial; España - Historia - <....-0414 (Edad antigua); República romana; Cuestores; Hispania; Antigua Roma; Provincias romanas